GUANINE CONTKNT OF SKIN OF SOME FISHES OF BOMBAY COAST - Manohar, S V (Indian Journal of Fisheries, 2011)
Among 13 fishes examined, Kati (Ilisha feligera) has the highest and Warn{Muraenesox talatonoides) the lowest amount of guanine in their skin (1,219 and115 mg guanine j>er 100 g skin). Muscle tissue contains no guanine.